Influence of Plasma Transfer Arc Cladding of NiCrBFe filler powder on microstructure and tensile properties of Titanium Grade 2 and Ti 6Al-4V alloy dissimilar joint prepared by laser beam welding. (August 2020) - Eswara Prasath, N.; Selvabharathi, R.
Highlights: Laser beam welding with Influence of Plasma Transfer Arc Cladding coated using TitaniumGrade2 and Ti6Al-4V sheet performed. Finite Element simulation able to predict tensile strength and weld quality. Plasma Transfer Arc Cladding coated enhanced fusion strength, owing-to α + β phase transformed into TiNi + TiCrFe boundaries. Abstract: The present investigation deals with the effect of Plasma Transfer Arc Cladding (PTAC) of 60%Ni30%CrB10%Fe filler powder on microstructure and tensile properties of Titanium Grade 2 and Ti 6Al-4V alloy dissimilar joint done by laser beam welding. In laser beam welding, full depth of penetration was achieved using the laser beam power of 1300 W, welding speed of 200 mm/min and focus distance of 10 mm. Tensile studies showed that all the failures occurred in the fusion zones of as-welded, dissimilar weldments and PTAC coated samples. Failure analysis was performed using Comsol software and the results were obsersed as well-in accordance with the experimental results. Finite element studies showed the better accuracy results while comparing both experiemental and simulation results. The microstructure and mechanical properties studies were conducted on as-welded, dissimilar weldments and PTAC coated samples by scanning electron microscope (SEM), transmission electron microscopy (TEM), energy dispersive spectrum (EDS), and X-ray diffraction (XRD) respectively. XRD displayed the slight presence of compressive residual stress in PTAC coated samples. The microstrcture studies conducted at the fusion zone revealed that more amount of coarse grain boundaries were converted into α-Fe. The avearge heat inputs (Hi) were applied in the coated samples that converted the α + β phase structure into TiNi + TiCrFe boundarys. PTAC coated samples showed the average hardness value of 313 HV and dissimilar weldments exhibited the hardness value of 290 HV. The present study concluded that the corrosion resistance of coated materials was improved owing to the better tensile and bending strength of material.